2017
DOI: 10.1002/icd.2036
|View full text |Cite
|
Sign up to set email alerts
|

Multigrade kindergarten classrooms and children's academic achievement, executive function, and socioemotional development

Arya Ansari

Abstract: Using data from the Early Childhood Longitudinal Study Kindergarten Class of 2010-2011 (ECLS-K: 2011; n = 11,000), this study examined the developmental outcomes of 5-year-old children in multi-grade classrooms (combined pre-kindergarten and kindergarten classrooms serving 3-, 4-, and 5-year-olds) compared with 5-year-olds attending kindergarten-only classrooms serving primarily 5-year-olds. Results from regression and propensity score analyses revealed that 5-year-old children who attended multi-grade classro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
4
0
3
Order By: Relevance
“…As such, as such, future work should seek to understand characteristics of children, families, teachers, classrooms, and schools that may be associated with divergent trajectories specifically in EF over time. For instance, relative disadvantages in early EF trajectories have been found for boys (Conway et al, 2018;Wiebe et al, 2008Wiebe et al, , 2012, children from low-SES or impoverished backgrounds (Conway et al, 2018), and relatively older children in mixed-age classrooms compared to children with same-age peers (Ansari, 2017).…”
Section: 2mentioning
confidence: 99%
“…As such, as such, future work should seek to understand characteristics of children, families, teachers, classrooms, and schools that may be associated with divergent trajectories specifically in EF over time. For instance, relative disadvantages in early EF trajectories have been found for boys (Conway et al, 2018;Wiebe et al, 2008Wiebe et al, , 2012, children from low-SES or impoverished backgrounds (Conway et al, 2018), and relatively older children in mixed-age classrooms compared to children with same-age peers (Ansari, 2017).…”
Section: 2mentioning
confidence: 99%
“…We focused on measures of academic achievement and executive function that have strong psychometric properties, are commonly used in middle childhood research, and have been previously shown to predict later outcomes within this sample (Ansari, 2017).…”
Section: Child Outcomesmentioning
confidence: 99%
“…Prior research has indicated that EF is associated with demographic factors such as age (e.g., Anderson, 2002) and socioeconomic status (e.g., Hackman et al, 2015); health-related factors such as disability status (e.g., Schoemaker et al, 2012) and physical activity levels (Best, 2010); and factors related to parent–child engagement such as disciplinary strategies (e.g., Fay-Stammbach et al, 2014) and frequency of parent–child interactions (e.g., Devine et al, 2016). In addition, school-level factors, such as presence of multigrade classrooms (Ansari, 2017) and school socioeconomic status are associated with child EF. Group differences in these factors that may be due to several potential causes such as opportunity gaps or cultural differences confound empirical evaluations of EF.…”
Section: Challenges and Implications Of Evaluating The Bilingual Adva...mentioning
confidence: 99%